EFEKTIVITAS ORGANISASIONAL - Indriastuti, Dorothea Ririn (Universitas Slamet Riyadi, 2012)
ABSTRACT This article review some of the research on organizational effectiveness has been done by several researchers theory of organization. The discussion starts from the view of traditional theory in the 1950 – 1960 to the modern view that has undergone improvements in the year 1970 – 1980. Several approaches have problems and weaknesses of each, so some of the models proposed can be utilized, although significantly, but very difficult to find the best due to the complexity of organizational effectiveness and each organization has different criteria. It is very difficult to produce a model that has the capability of high validity and generalizability. A model may be suitable for use in an organization but not necessarily suitable for use in other organizations. Keywords: organizational effectiveness, goal approach, functional approach